(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article delves into the profound influence of linguistic culture on literary expression, exploring how writers utilize language to evoke meaning, capture authenticity, and reflect the complexities of human experience. Through an examination of various aspects, including language as a reflective medium, its role in evoking atmosphere and setting, and its exploration of cultural identity and diversity, this study highlights the significance of linguistic culture in shaping the richness and depth of literary works. Additionally, the article discusses how writers subvert linguistic norms and conventions to create innovative forms of expression and preserve oral traditions and heritage. Ultimately, it argues that the multifaceted role of linguistic culture enriches the tapestry of literature, offering readers a deeper understanding of the world and ourselves.